Isolation of cytotoxic cycloartane triterpenoids from Dysoxylum malabaricum - Bhardwaj N.; Sharma V.K.; Tripathi N.; Pimpre K.; Sonti R.; Ravikanth G.; Koch B.; Jain S.K. (My University, 2025)
New cycloartane triterpenoids (2-4) have been recently discovered in the bark of Dysoxylum malabaricum. The extraction process involved the utilization of a cytotoxic dichloromethane-methanol extract, which underwent meticulous bioassay-guided fractionation employing high-performance liquid chromatography. A strategic LCMS-DNP-based dereplication approach was used to target the new compounds. Subsequently, the isolated compounds were thoroughly characterized utilizing nuclear magnetic resonance (NMR) and high-resolution electrospray ionization mass spectrometry (HRESIMS) data, and their absolute configurations were ascertained through electronic circular dichroism (ECD) calculations. In the context of biological activity, the compounds were evaluated for their cytotoxic potential against a panel of breast cancer cell lines and human normal embryonic kidney cancer cells. 2 demonstrated remarkable cytotoxicity, exhibiting an IC50 value of 18 μM against the T-47D breast cancer cell line, concurrently eliciting apoptotic cell death. The findings of this study emphasize the substantial potential of 2 as a promising candidate for further development as an anti-cancer agent. © 2024 The Royal Society of Chemistry.